Model Pengendalian Keuangan NGO yang Efektif pada Yayasan Eran Sangbure Mayang - Pea, Markus; Jaya, Amir; Rantererung, Corvis L. (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The internal control system plays a crucial role in ensuring accountability in financial management within NGOs. One of the main challenges often faced is the recruitment of staff who lack the necessary competence and understanding of financial management, as well as the lack of transparency in financial reporting, both within the organization and for stakeholders who require access to such reports. To ensure sustainability and prevent potential fraud, donors or funding bodies typically establish standards requiring that partner NGOs have transparent financial reports, published periodically, and audited by external parties. Therefore, an effective financial control system is needed to enable NGOs to authorize finances and control budgeting and expenditure in accordance with internal SOPs and the policies set by donors. Additionally, NGOs are advised to recruit staff with relevant educational qualifications, so that they are capable of performing tasks related to planning, implementation, and the preparation of financial reports in accordance with ISAK 335: Presentation of Financial Statements of Non-Profit Entities.